SAT0414 Development of malignancy in korean sjogren's syndrome patients; whole national health insurance data based analysis. (12th June 2018) - Lee, C.H.; Park, J.S.; Lim, H.S.; Pak, H.Y.
Abstract : Background: Though ocular and oral dryness are the main symptoms of Sjogren's syndrome, extraglandular manifestations including lymphoma were also developed. However, prevalence of Sjogren's syndrome was too low, most studies about lymphoma and malignancy were done on a small-scale. Objectives: For more large-scale research about development of malignancy in Sjogren's syndrome, we analysed this with whole Korean National Health Insurance data which include more than 95% of the population of the Republic of Korea. Methods: We compared the incidence of malignancy in newly diagnosed Sjogren's syndrome patients from 2004 to 2015 with age-sex matched controls and calculated hazard ratio (HR) with multiple Cox's model. Results: Among 198, 872 Sjogren's syndrome patients, cancer developed in 9883 patients (5% of newly diagnosed Sjogren's syndrome patients) after diagnosed Sjogren's syndrome. The duration from diagnosis of Sjogren's syndrome to development of malignancy was 5.4 year and their mean age was 55.2 years old. Malignancy incidence was higher in men, increased with age from the forties. It was also higher in patients who smoking or smoked, drinking more than 3times a week, and having history of malignancy (HR; 1.588, 95% CI; 1.405 1.794). The most common malignancy in patients with Sjogren's syndrome was thyroid cancer. The risk of overall malignancy was not higher than that of the control. However, the incidence of prostate cancer (HR; 1.339, 95% CI; 1.076 1.667), thyroid cancer (HR; 1.320, 95% CI; 1.093 1.594) and lymphoma (HR; 1.620, 95% CI: 1.066 2.462) were higher and hepatocellular carcinoma (HR; 0.591, 95% CI; 0.455 0.767) was lower than that of control. Lymphoma developed in 305 patients (3.1% of total malignancy); 10 cases of Hodgkin lymphoma, and 290 cases of non-Hodgkin lymphoma. Gender, age, smoking, drinking, body mass index, fasting blood glucose, and proteinuria were not significantly different from the control group in lymphoma development. Conclusions: Sjogren's syndrome patients' overall malignancy risk was not higher than that of control group. However, risk of lymphoma, prostate cancer, and thyroid cancer was higher than control group. Disclosure of Interest: None declared